Ethical Values and Biological Diversity: A Preliminary Assessment Approach - Joel I. Cohen (American Society for Microbiology, 2014)

(untitled)
There have been five major extinction events over geological time. However, the current rate of extinction or reduction of species and their habitats is directly related to anthropomorphic causes. For seventh grade students, biodiversity and its ethical considerations were introduced in a life sciences curriculum, following lessons on evolution, natural selection, and decent from common ancestry. This paper takes a preliminary look at the approach used in this unit, the ethical survey developed, and improvements to be made in subsequent years.